PEMBERIAN TRICHOKOMPOS JERAMI PADI DAN PUPUK FOSFOR TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KEDELAI (Glycine max (L.) Merrill) - Anjani, Nadia; Sjofjan, Jurnawaty; Puspita, Fifi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The research aims to know the effect of giving Trichokompos rice straw and phosphorus manure and to obtain the better dose for the growth and the product of soybean plants. The research used Random Design Group (RAK) that consists of two factors. The first factor is Trichokompos rice straw consists of four levels, such as 0 ton/ha (T0), 2,5 ton/ha (T1), 5 ton/ha (T2), 7,5 ton/ha (T3), and the second factor is phosphorus manure (TSP) that consists of three levels such as 0 kg/ha P2O5 (P0), 30 kg/ha P2O5 (P1), 60 kg/ha P2O5 (P2). The data gained has been analyzed by ANOVA and followed by Duncan’s multiple range test at the level of 5 %. The result showed that the combination treatment of Trichokompos rice straw and phosphorus manure gave no significant effect on all parameters of obvervation. Trichokompos rice straw 5 ton/ha and manure P2O5 60 kg/ha get the result that tend to be higher in the number of primary branch, dry weight of plants, the number of pithy pods per plant, the number of seeds per plant, seed product per m2, and the weight of 100 dry seeds. Keywords : Trichokompos rice straw, manure phosphorus, soybean